Harnessing carbon markets for tropical forest conservation: towards a more realistic assessment - Smith, J.; Mulongoy, K.; Persson, R.; Sayer, Jeffrey A. (2000)
The proposed Clean Development Mechanism (CDM) of the Kyoto Protocol paves the way for financial and technological transfers to support forestry projects that sequester carbon or protect carbon stocks. This paper examines the implications of CDM for forest conservation and sustainable use by drawing on recent literature and results of a Policy Dialogue with CDM stakeholders. Initial estimates of the contribution tropical forestry could make to climate change mitigation and forest conservation need to be scaled down and CDM payments are likely to be far more limited. The cost-effectiveness of forestry projects relative to projects in the energy sector may have been overestimated. Few estimates acknowledge that forests are unlikely to be conserved as long as the residency time of carbon in the atmosphere. Also political realities and investor priorities may not have been sufficiently understood. CDM funding for forestry may also decline as economically viable clean technologies are developed in the energy sector. Tropical forests provide an intermediate strategy to buy time until more permanent options are available. The most important justification for including forests in CDM may lie in its potential contribution to forest conservation and sustainable use. It is important to involve forest stakeholders more closely in the CDM debate. CDM projects may need to be limited to niches meeting certain political and institutional preconditions and where sufficient understanding of local decision-making and the broader context is available. There are pitfalls in using CDM to subsidise unprofitable forestry activities. The dangers of misusing CDM in relation to plantations, natural forest management and non-timber forest products are illustrated and examples given examples of how CDM could be harnessed for better use of forests. CDM is not a solution to the tropical forestry problem, but is a tool for enhancing forest conservation and sustainable use.